2002
DOI: 10.1074/jbc.m109673200
|View full text |Cite
|
Sign up to set email alerts
|

suREJ3, a Polycystin-1 Protein, Is Cleaved at the GPS Domain and Localizes to the Acrosomal Region of Sea Urchin Sperm

Abstract: The sea urchin sperm acrosome reaction (AR) is a prerequisite for sperm-egg fusion. This report identifies sea urchin sperm receptor for egg jelly-3 (suREJ3) as a new member of the polycystin-1 family (the protein mutated in autosomal dominant polycystic kidney disease). suREJ3 is a multidomain, 2,681-amino acid, heavily glycosylated orphan receptor with 11 putative transmembrane segments (TMS) that localize to the plasma membrane covering the sperm acrosomal vesicle. Like the latrophilins and other members of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 50 publications
1
67
0
Order By: Relevance
“…The apparent asynchronous behavior of mammalian spermatozoa coupled with the paucity of female gametes (eggs) prompted many to use invertebrate animal models to understand the molecular basis of fertilization (29,30). Functional bioassays allowed identification of important signaling components in the invertebrate sperm cells, and the subsequent identification of homologous genes in the mammal seemed a strong approach for unraveling fertilization mechanisms in the mammal.…”
Section: Resultsmentioning
confidence: 99%
“…The apparent asynchronous behavior of mammalian spermatozoa coupled with the paucity of female gametes (eggs) prompted many to use invertebrate animal models to understand the molecular basis of fertilization (29,30). Functional bioassays allowed identification of important signaling components in the invertebrate sperm cells, and the subsequent identification of homologous genes in the mammal seemed a strong approach for unraveling fertilization mechanisms in the mammal.…”
Section: Resultsmentioning
confidence: 99%
“…We searched the predicted protein sequence of BAI1 using Simple Modular Architecture Research Tool (SMART) for consensus sequence of known proteolytic cleavage sites and identified a G-protein-coupled receptor proteolytic cleavage site (GPS) at the junction of the N-terminal extracellular region with the first transmembrane domain (Figure 1a). GPS domains are approximately 50 residues long containing either two or four conserved cysteinecs and are found by sequence homology in otherwise functionally unrelated receptors including latrophilin-1 (CL1), hCD97, Flamingo-1, sea urchin sperm receptor for egg jelly (suREJ3) and Ig Hepta (Gray et al, 1996;Krasnoperov et al, 2002;Mengerink et al, 2002). Alignment of the GPS domains in BAI1 and other GPS-containing receptors is shown in Figure 1c.…”
Section: Domain Analysis Of Brain Angiogenesis Inhibitormentioning
confidence: 99%
“…Peptide Sequencing and Sequence Analysis-Several high molecular weight proteins are enriched in WGA eluates of solubilized sperm protein when compared with the starting material, including suREJ1 and suREJ3 (6,7). The 220-kDa band is enriched in the eluate and can also be detected in the starting material (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Antibody Production-A portion of suABCA DNA corresponding to Ala 961 -Pro 1158 was ligated into the pET15b vector (Novagen), which contains an NH 2 -terminal His tag, and bacterially expressed according to a previously published protocol (7). The resulting purified recombinant protein, ABCe, was separated by SDS-PAGE and negatively stained with cupric chloride (20).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation